Li-Fi technology-based long-range FSO data transmit system evaluation - Faruq, Omar; Shahriar Rahman, Kazi Rubaiyat; Jahan, Nusrat; Rokoni, Sakib; Rabeya, Mosa (Sustainable Engineering and Innovation, 2023)
Visible light is used by a technology known as Light Fidelity to establish wireless internet connections very quickly. This article offers line-of-sight communication between the transmitter and receiver using LED technology. Li-Fi technology is a method that transmits data using LED light, which is faster and more efficient than Wi-Fi. Since it is practically ubiquitous, light can be used for communication as well. A cutting-edge technology called optical communication includes a subset called Li-Fi. By sending out visible light, the Li-Fi device enables wireless intranet communication. An in-depth study and analysis of Li-Fi, a novel technology that transmits data at high speeds over a wide spectrum by using light as a medium of transmission.